Perubahan Makna pada Kata Serapan Bahasa Arab dalam Bahasa Indonesia - Muiz, Abdul; Nu'man, Mohammad (Armala, 2024)
Arabic has become one of the sources for the enrichment of Indonesian vocabulary through the influence of religion and cultural interaction over the centuries. Many vocabulary items from Arabic have been absorbed and used in Indonesian. However, many of the absorbed words in Indonesian have now undergone changes in meaning when used in the Indonesian language. The change in meaning of loanwords is often influenced by social and cultural factors, differences in fields of usage, associations, term development, and communication needs in Indonesian society. This study focuses on examining various changes in meaning in loanwords from Arabic, both semantically and pragmatically. These changes may include narrowing, broadening, amelioration, pejoration, or even a total shift in meaning. This research uses a qualitative descriptive method by examining loanwords through texts and the context of usage in the Indonesian language. This study is expected to provide further insights into the dynamics of language evolution and how social context influences the development of word meanings in a language.